Harvest and postharvest brown rot of fruit in relation to early latent infection caused by Monilinia spp. in Hungary - Holb, I. J. (International Journal of Horticultural Science, 2015)
In this study, the effect of early latent infection caused by Monilina spp. on harvest and postharvest brown rot of sour cherry and peach was investigated. Two field experiments were performed in commercial orchards located at Eperjeske on sour cherry and at Siófok on peach in 2013 and 2014 in order to study the possible relationship between the incidence of early latent infection caused by Monilinia spp. and the incidence of harvest and postharvest brown rot. No latent infection was recorded at popcorn phanological stage of the trees at both locations. The maximum incidence was detected during the pit hardening period. There was a positive correlation between the incidence of latent infection and harvest or postharvest brown rot. The average incidence of latent infection during the crop season explained approximatelly 20% of the total variation in the incidence of postharvest brown rot.